Organic matter and nitrogen studies in Malaysian soils - Yaacob, Othman; Tan, Keh Huat; Tham, Kah Cheng (1979)
The natural distribution of organic matter (OM) and nitrogen (N) in selected eco-system and some problem soils is outlined. The influence of clearing, burning and cropping on the levels of OM and N is also discussed. The effective use of legume and natural covers in regulating and maintaining the amount of OM and N in selected plantation crops is compared and discussed along with the use of fertilizer N in wet rice cultivation and annual crop production on arable soils. More adequate management of crop residue and organic matter on intensive legume-based crop system on soils (Oxisole and Utisole) is also outlined.